Staatliche Beihilfen und Beihilfenkontrolle im Agrarsektor - Johannes Paha; Anna-Lena Zwerenz (Wirtschaftsdienst, 2013)
Die Mitgliedstaaten der EU gewährten 2010 Agrarbeihilfen in Höhe von 10,3 Mrd. Euro. Die derzeitige Rahmenregelung zur Kontrolle von Agrarbeihilfen läuft im Dezember 2013 aus und muss für 2014 bis 2020 neu gefasst werden. Dies bietet die Gelegenheit einer Neuausrichtung. Die Autoren vertreten die Auffassung, dass ökonomische Analysemethoden, die in der Beihilfenkontrolle in nichtlandwirtschaftlichen Sektoren verstärkt Anwendung finden, auch auf Agrarbeihilfen angewendet werden sollten. – – In 2010, EU member states granted worth exteuro10.3bn aid to their agricultural sector. Given the requirement to revise the guidelines for state aid in the agricultural sector by the end of 2013, this article presents the legal rules and facts of this topic from an economic point of view. It is shown that economic methods which have been increasingly used in state aid control for non-agricultural sectors since 2005 can also be used for the analysis of state aid in the agricultural sector. Additional research is required to further develop these methods and establish the benefi ts of their application.
Keywords: H20; L49; Q14; 330; EU-Agrarpolitik; Agrarsubvention; EU-Beihilfenkontrolle; Wirkungsanalyse; EU-Staaten